2009
DOI: 10.1002/eat.20681
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure of the eating disorder examination in clinical and community samples

Abstract: Overall, there was more support for a one-factor model of EDE data than for a multi-factorial model. It may be more appropriate to use Global EDE scores than individual subscale scores for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 18 publications
8
100
2
Order By: Relevance
“…Only the Restraint subscale from the EDE-Q was used in the present analyses. Previous research indicates that the EDE-Q demonstrates acceptable internal consistency (Cronbach's alpha ranging from .77 to .84) (Byrne, Allen, Lampard, Dove, & Fursland, 2010), and good convergent validity with the EDE interview (Black & Wilson, 1996;Fairburn & Beglin, 2008) and criterionrelated validity for distinguishing obese individuals who engage in binge eating from individuals who do not binge eat (Wilson, Nonas, & Rosenblum, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Only the Restraint subscale from the EDE-Q was used in the present analyses. Previous research indicates that the EDE-Q demonstrates acceptable internal consistency (Cronbach's alpha ranging from .77 to .84) (Byrne, Allen, Lampard, Dove, & Fursland, 2010), and good convergent validity with the EDE interview (Black & Wilson, 1996;Fairburn & Beglin, 2008) and criterionrelated validity for distinguishing obese individuals who engage in binge eating from individuals who do not binge eat (Wilson, Nonas, & Rosenblum, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…combining the subscales) were not made using CFA. For the three-factor model presented by Byrne et al [23], fit statistics indicated that the model did not fit the data well and standardised factor loading estimates revealed that not all indicators were strongly related to the latent factors (range=0.214 to 0.782).…”
Section: Cfamentioning
confidence: 96%
“…Given the poor original factor structure of the EDE and EDE-Q evident in this study and reported in previous studies [18][19][20]23], a three-factor model was tested as outlined by Byrne et al [20] was interpreted as restraint, eating concern and weight and shape concern. An alternative four-factor model proposed by Hrabosky et al [18] was not tested as it included additional behavioural frequency items that were not part of the original scales.…”
Section: Cfamentioning
confidence: 99%
See 2 more Smart Citations